Association Between Digoxin Use and Cardiac Function in Infants With Single-Ventricle Congenital Heart Disease During the Interstage Period. Issue 6 (11th April 2022) - Kumar, Karan R.; Flair, Antonina; Thompson, Elizabeth J.; Zimmerman, Kanecia O.; Andersen, Nicholas D.; Hill, Kevin D.; Hornik, Christoph P.
Abstract : OBJECTIVES: To examine the association between digoxin use and cardiac function assessed by echocardiographic indices in infants with single-ventricle (SV) congenital heart disease (CHD) during the interstage period. DESIGN: Retrospective cohort study. SETTING: Fifteen North American hospitals. PATIENTS: Infants discharged home following stage 1 palliation (S1P) and prior to stage 2 palliation (S2P). Infants with no post-S1P and pre-S2P echocardiograms were excluded. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Of 373 eligible infants who met inclusion criteria, 140 (37.5%) were discharged home on digoxin. In multivariable linear and logistic regressions, we found that compared with infants discharged home without digoxin, those discharged with digoxin had a smaller increase in end-systolic volume (β = –8.17 [95% CI, –15.59 to –0.74]; p = 0.03) and area (β = –1.27 [–2.45 to –0.09]; p = 0.04), as well as a smaller decrease in ejection fraction (β = 3.38 [0.47–6.29]; p = 0.02) and fractional area change (β = 2.27 [0.14–4.41]; p = 0.04) during the interstage period. CONCLUSIONS: Digoxin may partially mitigate the expected decrease in cardiac function during the interstage period through its positive inotropic effects. Prospective clinical trials are needed to establish the pharmacokinetics, safety, and efficacy of digoxin use in SV CHD.